2016
DOI: 10.1007/s12665-015-4846-0
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the wind direction and plants on the variability of topsoil magnetic susceptibility in industrial and urban areas of southern Poland

Abstract: Volume magnetic susceptibility (j) was measured on the soil surface and in the vertical topsoil profile within a 300 km 2 area located in an urban-industrial conurbation. The results were compared to plant species compositions in the forest storeys, elevation above sea level, and terrain geomorphology. The content and mineral composition of the magnetic fraction were determined in the soil horizons. It was found that the extent of the area with enhanced topsoil magnetic susceptibility was similar to the domina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…The dust formed in the process of coal combustion at the Rybnik power plant contains on average 120 mg kg −1 Zn, 64 mg kg −1 Cr, 40 mg kg −1 of each Cu, Ni, and Pb and 3 mg kg −1 Cd (Smołka-Danielowska 2006). The elevated content of heavy metals in the soils of the study site has been confirmed by earlier research (Magiera et al 2015;Magiera et al 2016). The field sites were located in forest complex east of Rybnik where the soils are derived from glacial moraines and are dominated by Brunic Arenosols and Cambisols (WRB 2014).…”
Section: Study Area and Soil Samplingsupporting
confidence: 75%
“…The dust formed in the process of coal combustion at the Rybnik power plant contains on average 120 mg kg −1 Zn, 64 mg kg −1 Cr, 40 mg kg −1 of each Cu, Ni, and Pb and 3 mg kg −1 Cd (Smołka-Danielowska 2006). The elevated content of heavy metals in the soils of the study site has been confirmed by earlier research (Magiera et al 2015;Magiera et al 2016). The field sites were located in forest complex east of Rybnik where the soils are derived from glacial moraines and are dominated by Brunic Arenosols and Cambisols (WRB 2014).…”
Section: Study Area and Soil Samplingsupporting
confidence: 75%
“…A significant increase in the amount of pollutants deposited as a result of emissions, including Cd, Ni, and Pt, was indicated. Research conducted in the area of the Upper Silesian agglomeration revealed a significant relationship between the magnitude of magnetic susceptibility and the degree of transformation of soils, including technogenic and urban soils (Strzyszcz et al 1994;Łukasik et al, 2015;Magiera et al, 2016aMagiera et al, , 2016b.…”
Section: Technogenic Soils In Urban Areasmentioning
confidence: 99%